Downfall : a brady novel of suspence - Jance, Judith A., 1944- (William Morrow Fiction ., 2017)
A puzzling new case has just hit Sheriff Joanna Brady's department, demanding every resource she has at her disposal-as well as help from neighboring law enforcement agencies and the Feds. The bodies of two women have been found at the base of a nearby peak, known to Bisbee locals as Geronimo. Is this a terrible accident, a case of murder/suicide, or a double homicide?